A highly sensitive imaging polarimeter in the X-ray regime - Grabiger, Benjamin; Marx-Glowna, Berit; Uschmann, Ingo; Loetzsch, Robert; Paulus, Gerhard G.; Schulze, Kai S. (Applied Physics Letters, 2020)
We report on the development of a highly sensitive imaging polarimeter that allows for the investigation of polarization changing properties of materials in the X-ray regime. By combining a microfocus rotating anode, collimating multilayer mirrors, and two germanium polarizer crystals, we achieved a polarization purity of the two orthogonal linear polarization states of 8 × 10-8. This enables the detection of an ellipticity on the same order or a rotation of the polarization plane of 6 arcsec. The high sensitivity combined with the imaging techniques allows us to study the microcrystalline structure of materials. As an example, we investigated beryllium sheets of different grades, which are commonly used for fabricating X-ray lenses, with a spatial resolution of 200 μm, and observed a strong degradation of the polarization purity due to the polycrystalline nature of beryllium. This makes X-ray lenses made of beryllium unsuitable for imaging polarimeter with higher spatial resolution. The results are important for the development of X-ray optical instruments that combine high spatial resolution and high sensitivity to polarization.
CRIS-Team Scopus Importer:2023-04-20